COMPLETE RUPTURE OF THE UTERUS ALONG THE PREVIOUS SCAR DURING PREGNANCY - Валентина Ивановна Черняева; Наталья Николаевна Гончарова; Оксана Николаевна Новикова; Татьяна Юрьевна Марочко; Ольга Александровна Зотова; Елена Александровна Шакирова; Мария Николаевна Сурина; Вадим Гельевич Мозес; Ольга Борисовна Карелина (Мать и дитя в Кузбассе, 2020)
Describes the clinical observation of a complete rupture of the uterus along the previous scar during pregnancy of 39-40 gestation weeks in a patient with a burdened obstetric and gynecological history outside the hospital. The patient was undergo surgical operation for emergency indications after 10 minutes from the moment of admission to the hospital. Timely assistance provided predetermined a favorable outcome for the mother and fetus.